Randomized trial of safinamide add‐on to levodopa in Parkinson's disease with motor fluctuations. Issue 2 (9th December 2013) - Borgohain, Rupam; Szasz, J.; Stanzione, P.; Meshram, C.; Bhatt, M.; Chirilineau, D.; Stocchi, F.; Lucini, V.; Giuliani, R.; Forrest, E.; Rice, P.; Anand, R.; et al.
ABSTRACT Levodopa is effective for the motor symptoms of Parkinson's disease (PD), but is associated with motor fluctuations and dyskinesia. Many patients require add‐on therapy to improve motor fluctuations without exacerbating dyskinesia. The objective of this Phase III, multicenter, double‐blind, placebo‐controlled, parallel‐group study was to evaluate the efficacy and safety of safinamide, an α‐aminoamide with dopaminergic and nondopaminergic mechanisms, as add‐on to l‐dopa in the treatment of patients with PD and motor fluctuations. Patients were randomized to oral safinamide 100 mg/day (n = 224), 50 mg/day (n = 223), or placebo (n = 222) for 24 weeks. The primary endpoint was total on time with no or nontroublesome dyskinesia (assessed using the Hauser patient diaries). Secondary endpoints included off time, Unified Parkinson's Disease Rating Scale (UPDRS) Part III (motor) scores, and Clinical Global Impression‐Change (CGI‐C). At week 24, mean ± SD increases in total on time with no or nontroublesome dyskinesia were 1.36 ± 2.625 hours for safinamide 100 mg/day, 1.37 ± 2.745 hours for safinamide 50 mg/day, and 0.97 ± 2.375 hours for placebo. Least squares means differences in both safinamide groups were significantly higher versus placebo. Improvements in off time, UPDRS Part III, and CGI‐C were significantly greater in both safinamide groups versus placebo. There were no significant between‐group differences for incidences of treatment‐emergent adverse events (TEAEs) or TEAEs leading to discontinuation. The addition of safinamide 50 mg/day or 100 mg/day to l‐dopa in patients with PD and motor fluctuations significantly increased total on time with no or nontroublesome dyskinesia, decreased off time, and improved parkinsonism, indicating that safinamide improves motor symptoms and parkinsonism without worsening dyskinesia. © 2013 International Parkinson and Movement Disorder Society